Stochastic Dominance and Nonparametric Comparative Revealed Risk Aversion - Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
It is shown how to test revealed preference data on choices under uncertainty for consistency with first and second order stochastic dominance (FSD or SSD). The axiom derived for SSD is a necessary and sufficient condition for risk aversion. If an investor is risk averse, stochastic dominance relations can be combined with revealed preference relations to recover a larger part of an investor's preference. Interpersonal comparison between investors can be based on intersections of revealed preferred and worse sets. Using a variant of Yaari's (1969) defi nition of more risk averse than, it is shown that it is sufficient to compare only the revealed preference relations of two investors. This makes the approach operational given a finite set of observations. The central rationalisability theorem provides strong support for this approach to comparative risk aversion. The entire analysis is kept completely nonparametric and can be used as an alternative or complement to parametric approaches and as a robustness check. The approach is illustrated with an application to experimental data of by Choi et al. (2007). Most subjects come close to SSD-rationality, and most subjects are comparable with each other. The distribution of risk attitudes in the population can be described by comparing subjects' choices with any given preference, which is also illustrated. – – Dieser Artikel zeigt zunächst, wie Daten zu Entscheidungen unter Unsicherheit auf Konsistenz mit stochastischer Dominanz in erster und zweiter Ordnung (FSD bzw. SSD) getestet werden können. Wenn ein Investor SSD-rational ist, können die SSD-Relation und die offenbarte Präferenzrelation kombiniert werden, um einen größeren Teil der Präferenzen des Investors zu rekonstruieren. Interpersonelle Vergleiche zwischen Investoren können auf Basis von Schnittmengen der Besser- und Schlechtermengen der Investoren vorgenommen werden. Basierend auf Yaaris (1969) risikoaverser als-Relation wird gezeigt, dass ein Vergleich der endlichen offenbarten Präferenzrelationen hinreichend ist; der Ansatz ist daher operational. Die Analyse ist vollständig nichtparametrisch und kann als Alternative oder Ergänzung zu parametrischen Ansätzen und als Robustheitsprüfung angewandt werden. Der Ansatz wird mit experimentellen Daten von Choi et al. (2007) illustriert. Die meisten Probanden kommen SSD-Rationalität sehr nahe und sind miteinander vergleichbar. Die Verteilung von Riskoeinstellungen kann durch den Vergleich der Probanden mit jeder beliebigen Präferenz beschrieben werden, was ebenfalls illustriert wird.
Keywords: C14; C91; D11; D12; 330; Comparative risk aversion; experimental economics; induced budget experiments; interpersonal comparison; nonparametric analysis; portfolio choice; revealed preference; risk preference; Comparative risk aversion; experimental economics; induced budget experiments; interpersonal comparison; nonparametric analysis; portfolio choice; revealed preference; risk preference